PSO based Optimal Power Flow for Optimal Placement and Sizing of Static VAR Compensator - Kumar, K.Vinodh; Kumar, B.Sravan (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
In recent years, the transmission lines are stressed heavily, hence there is a risk with leads to voltage instability in the power system. Hence it is difficult to operate the power system in order to maintain stable power supply. It will leads to major problems like voltage instability and power losses. Flexible AC Transmission System (FACTS) has been implemented in power system to overcome such problems. By placing these devices in suitable location, optimal power flow can be obtained. In this paper, Particle Swarm Optimization (PSO) is used to optimize the location of the FACTS devices as a shunt controller, Static VAR Compensator (SVC) is been taken under consideration for this paper. PSO is an iterative procedure solving multi objective optimization problems to obtain an optimal solution. Hear IEEE 14 bus system is considered for finding the optimal location and rating of SVC using PSO.